Luis Saslavsky, director y novelista. - SETTON, ROMÁN (Bulletin of Hispanic Studies (1475-3839), 2015)
In contrast to the flm work of Luis Saslavsky, his literature is almost completely unknown. This paper analyses the crime novel A sangre fríalIn Cold Blood which so far has received no critical attention. Such an inquiry is made in light of the history of the detective novel in Argentina and in disagreement with the offcial history of the genre. I also analyse the novel in connection with the author's flm work and, more generally, in connection with the crime flm and flm noir of the time. I hold the view that, as in the feld of cinema, Saslavsky's literature also contrasts sharply with the genre conventions of the time: in particular in this novel, Saslavsky makes a pragmatic use (Altman) of the hard-boiled school and some topics of the flm noir tradition.